Facilitation of on-line learning environments: what works when teaching distance learning computer science students - Tina Wilson; Denise Whitelock (Information Research: An International Electronic Journal)
Educationalists worldwide are seeking to adopt on-line systems to improve their course presentations. This raises a number of issues, about how these on-line systems can best be integrated and also what structures and resources need to be put in place to support such an approach. This paper will discuss how the M205 - STILE project was supported at the Open University in 1995 and discuss the tutors responses about the advantages and disadvantages of the on-line presentation of the course as compared to face to face tutorials.